2015
DOI: 10.3762/bjoc.11.121
|View full text |Cite
|
Sign up to set email alerts
|

Indolizines and pyrrolo[1,2-c]pyrimidines decorated with a pyrimidine and a pyridine unit respectively

Abstract: SummaryThe three possible structural isomers of 4-(pyridyl)pyrimidine were employed for the synthesis of new pyrrolo[1,2-c]pyrimidines and new indolizines, by 1,3-dipolar cycloaddition reaction of their corresponding N-ylides generated in situ from their corresponding cycloimmonium bromides. In the case of 4-(3-pyridyl)pyrimidine and 4-(4-pyridyl)pyrimidine the quaternization reactions occur as expected at the pyridine nitrogen atom leading to pyridinium bromides and consequently to new indolizines via the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[27][28][29][30] Usually, this multistep process starts with the preparation of N-heterocyclic quaternary salts with -halo carbonyl compounds, in situ conversion into corresponding heterocyclic N-ylides in the presence of an inorganic or organic base and 3+2 dipolar cycloaddition reactions of heterocyclic N-ylides with electron-deficient alkynes or alkenes. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Our group has developed a simple one-pot, multicomponent synthetic strategy towards N-bridgehead heterocyclic compounds based on the consecutive quaternization of the N-heteroaromatic compound, in situ generation of the heterocyclic N-ylide, 3+2 dipolar cycloaddition reaction to an electron-deficient alkyne and aromatization sequence, using an epoxide as solvent and acid scavenger. [46][47][48][49][50][51][52][53][54][55] A range of new indolizines and azaindolizines were synthesized via 3+2 dipolar cycloaddition reactions of cycloimmonium ylides, generated from the various N-heterocycles such as pyridine, quinoline, isoquinoline, pyridazine, pyrimidine, phthalazine and benzimidazole derivatives with diverse phenacyl bromides, alkyl bromoacetates, 3-(2-bromoacetyl)-2H-chromen-2-one and electrondeficient alkynes.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Usually, this multistep process starts with the preparation of N-heterocyclic quaternary salts with -halo carbonyl compounds, in situ conversion into corresponding heterocyclic N-ylides in the presence of an inorganic or organic base and 3+2 dipolar cycloaddition reactions of heterocyclic N-ylides with electron-deficient alkynes or alkenes. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Our group has developed a simple one-pot, multicomponent synthetic strategy towards N-bridgehead heterocyclic compounds based on the consecutive quaternization of the N-heteroaromatic compound, in situ generation of the heterocyclic N-ylide, 3+2 dipolar cycloaddition reaction to an electron-deficient alkyne and aromatization sequence, using an epoxide as solvent and acid scavenger. [46][47][48][49][50][51][52][53][54][55] A range of new indolizines and azaindolizines were synthesized via 3+2 dipolar cycloaddition reactions of cycloimmonium ylides, generated from the various N-heterocycles such as pyridine, quinoline, isoquinoline, pyridazine, pyrimidine, phthalazine and benzimidazole derivatives with diverse phenacyl bromides, alkyl bromoacetates, 3-(2-bromoacetyl)-2H-chromen-2-one and electrondeficient alkynes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was of interest to prepare analogous compounds containing a pyrroloazine directly attached to the C-4 position of a sydnone ring. From a survey of the literature data [615] and based on our previous findings [1619] it was concluded that the heterocycle in the pyrroloazine series most suitable for this study would be indolizine ( 2 ).…”
Section: Introductionmentioning
confidence: 99%